Biomarkers and their potential for detecting livestock plant poisonings in Western North America - Green, Benedict T.; Welch, Kevin D.; Lee, Stephen T.; Stonecipher, Clinton A.; Gardner, Dale R.; Stegelmeier, Bryan L.; Davis, T. Zane; Cook, Daniel (Frontiers in Veterinary Science, 2023)
The United States National Cancer Institute defines a biomarker as: “A biological molecule found in blood, other body fluids, or tissues that is a sign of a normal or abnormal process, or of a condition or disease...” In Veterinary Medicine, biomarkers associated with plant poisonings of livestock have great utility. Since grazing livestock poisoned by toxic plants are often found dead, biomarkers of plant poisoning allow for a more rapid postmortem diagnosis and response to prevent further deaths. The presence and concentration of toxins in poisonous plants are biomarkers of risk for livestock poisoning that can be measured by the chemical analysis of plant material. More difficult is, the detection of plant toxins or biomarkers in biological samples from intoxicated or deceased animals. The purpose of this article is to review potential biomarkers of plant poisoning in grazing livestock in the western North America including recently investigated non-invasive sampling techniques. Plants discussed include larkspur, lupine, water hemlock, swainsonine-containing plants, selenium-containing plants, and pyrrolizidine alkaloid containing plants. Other factors such as animal age and sex that affect plant biomarker concentrations in vivo are also discussed.